Modelling analysts’ target price revisions following good and bad news? /Ho Q Tuan, Norman Strong, Martin Walker. - Ho, Q. Tuan.
We study the relation between analysts’ target price revisions and recent market returns, excess stock returns, and other analysts’ target price revisions. Empirical results show that, after controlling for earnings forecast and recommendation revisions, target price revisions are associated with each of these information sources. We also find that target price revisions are more sensitive to negative than to positive excess stock returns. We conjecture that firms’ tendency to withhold bad news, while releasing good news promptly, drives this effect and, using proxies for firms’ withholding of bad news, we report evidence supporting this hypothesis.